Manajemen Konflik Hubungan Long Distance Relationship - Meidina Tazqia Azzahra; Mochammad Rochim (Bandung Conference Series: Public Relations, 2024)
Abstract. Long distance relationships between husband and wife are something that usually happens because of work, this research uses qualitative research methods, where there are factors that can trigger conflict due to the distance that separates husband and wife, when a long distance relationship occurs it will trigger conflict. There is a resolution of a problem which is called conflict management, in every relationship there are different ways of resolving conflict in each husband and wife relationship which is called conflict management style, a case study of the women's civil servants' organization Samsat Soreang, the purpose of this research is to find out how each married couple resolves conflicts, managing conflicts in conflict management styles. Using qualitative methods with interview techniques via WhatsApp. Abstrak. Hubungan jarak jauh diantara suami istri adalah hal yang biasa terjadi karena pekerjaan, penelitian ini mengunakan metode penelitian kualitatif, yang dimana terdapat faktor yang dapat memicu terjadinya konflik dikarenakan jarak yang memisahkan antara suami dan istri, ketika terjadinya hubungan jarak jauh akan memicu konflik dalam konflik akan terjadi sebuah penyelesaian suatu masalah yang dinamakan manajemen konflik, dalan setiap hubungan terdapat cara penyelesaian konflik yang berbeda-beda pada setiap hubungan suami istri yang disebut gaya manajemen konflik, studi kasus pada organisasi istri pegawai negri sipil darma wanita samsat cibinong. Tujuan dari penelitian ini untuk mengetahui cara penyelesaian konflik setiap pasangan suami istri, memanajemen sebuah konflik yang terdapat dalam gaya manajemen konflik. Mengunakan metode kualitatif dengan teknik wawancara via whatsapp.